2017
DOI: 10.1055/s-0043-104383
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Betatrophin Levels of Subjects Classified with Normal, Impaired, and Diabetic Glucose Tolerance, and Subjects with Impaired Fasting Glucose

Abstract: This study was aimed to investigate whether betatrophin shows glucose intolerance or not. To access the plasma betatrophin levels after basal and glucose load, groups were classified as normal glucose tolerance (NGT), impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and diabetic glucose tolerance (DGT) according to WHO 2012 criteria. An oral glucose tolerance test was performed on age-matched subjects (n=220) with a body mass index (BMI)<27 kg/m. Subjects were categorized as normoglycemic (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, several researchers have raised a concern regarding the potential influence of glycemic status differences on betatrophin levels [36, 37]. Stratified subgroup analyses were conducted to evaluate between-study variations in glycemic status.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several researchers have raised a concern regarding the potential influence of glycemic status differences on betatrophin levels [36, 37]. Stratified subgroup analyses were conducted to evaluate between-study variations in glycemic status.…”
Section: Discussionmentioning
confidence: 99%
“…IFG was defined as FPG of 110 mg/dL (6.1 mmol/L) to <125 mg/dL (7.0 mmol/L) based on WHO criteria. 20,21 Disease definition. Nonalcoholic fatty liver disease (NAFLD) was diagnosed based on abdominal ultrasonography findings plus the exclusion of alcohol consumption, viral infection, or autoimmune liver disease.…”
Section: Methodsmentioning
confidence: 99%
“…The negative association between betatrophin concentrations and BCS in the healthy dogs is different from reported increased betatrophin in obesity in most reports in humans, 12 although decreased concentrations in obesity or no difference between lean to and obese individuals were reported in a few studies in humans, 42,43 and it was suggested that this heterogeneity partially could be explained by glycemic status. 12 In non-obese human subjects, betatrophin concentrations were increased with impaired glucose tolerance, 44 suggesting the increase in betatrophin in obesity might be attributed, at least partially to glucose intolerance. Therefore, the different alteration in betatrophin in obesity in dogs might be attributed to the fact that obese dogs do not become glucose intolerant despite long-standing insulin resistance.…”
Section: Discussionmentioning
confidence: 99%